2020
DOI: 10.1007/s10973-020-09789-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of unsteady mixed convection of Cu–water nanofluid in an oscillatory, lid-driven enclosure using lattice Boltzmann method

Abstract: The unsteady physics of laminar mixed convection in a lid-driven enclosure filled with Cu-water nanofluid is numerically investigated. The top wall moves with constant velocity or with a temporally sinusoidal function, while the other walls are fixed. The horizontal top and bottom walls are, respectively, held at the low and high temperatures, and the vertical walls are assumed to be adiabatic. The governing equations along with the boundary conditions are solved through D2Q9 fluid flow and D2Q5 thermal lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Solar collectors require structural changes as well as efficient geometry. Over the last few decades, global warming, ozone layer depletion, and rising sea levels have been just a few of the irreversible environmental consequences of human activity [ 120 , 121 ]. In recent years, many modifications have tried to improve the efficiency of solar systems.…”
Section: Effect Of Cavities In Solar Collectorsmentioning
confidence: 99%
“…Solar collectors require structural changes as well as efficient geometry. Over the last few decades, global warming, ozone layer depletion, and rising sea levels have been just a few of the irreversible environmental consequences of human activity [ 120 , 121 ]. In recent years, many modifications have tried to improve the efficiency of solar systems.…”
Section: Effect Of Cavities In Solar Collectorsmentioning
confidence: 99%
“…They discovered that the heat transfer rate drops when the Hartmann number rises and that as the Richardson number increases, the Nusselt number rises, and the heat transfer rate is enhanced. Using the lattice Boltzmann method, Valizadeh Ardalan et al (2021) tackled the problem of mixed convection inside an oscillatory lid-driven cavity. It was observed that lowering the Ri and increasing the volume fraction lead to an improvement in the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully applied as a new alternative to solve complex fluid flow problems as thermal flows [8], micro flows [9], multiphase flows [10] and fluid-interactions [11]. The LBM has been extended to simulate nanofluids flow [12,13]. The present numerical study is motivated by the success of recent developments of nanofluid flow simulation by using the LBM method.…”
Section: Introductionmentioning
confidence: 99%